2015
DOI: 10.1038/jid.2015.194
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Action Spectrum of UVR-Induced Mitochondrial DNA Damage in Human Skin Cells

Abstract: Biological responses of human skin to UVR including cancer and aging are largely wavelength-dependent, as shown by the action spectra of UVR-induced erythema and nuclear DNA (nDNA) damage. A molecular dosimeter of UVR exposure is therefore required. Although mitochondrial DNA (mtDNA) damage has been shown to be a reliable and sensitive biomarker of UVR exposure in human skin, its wavelength dependency is unknown. The current study solves this problem by determining the action spectrum of UVR-induced mtDNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Unfortunately, some ophthalmic lens standards still ignore this invisible hazard of UVR wavelengths, especially the ones longer than 380 nm, thus creating an UVR protection void. However, UVR between 380 and 400 nm is abundant in the solar UVR spectrum , and UVR hazard from these wavelengths have been reported in numerous recent works . Therefore, we adopted the most widely used definition of UVR extending up to 400 nm, first described by the ICNIRP .…”
Section: Uvr Protection Highlightsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, some ophthalmic lens standards still ignore this invisible hazard of UVR wavelengths, especially the ones longer than 380 nm, thus creating an UVR protection void. However, UVR between 380 and 400 nm is abundant in the solar UVR spectrum , and UVR hazard from these wavelengths have been reported in numerous recent works . Therefore, we adopted the most widely used definition of UVR extending up to 400 nm, first described by the ICNIRP .…”
Section: Uvr Protection Highlightsmentioning
confidence: 99%
“…This adoption is in line with the recommendations adopted by the World Health Organization (WHO) , while other organizations like the American National Standards Institute still keep the 380 nm limit. The adoption of UVR limit is important since in a study by Latimer et al it was shown that when the ICNIRP‐UVR action spectrum was weighted by the solar UVR spectrum adopted in ISO 8980‐3 , where the 380 nm limit is also considered, the results (Figure ) suggested that a much larger threat exists from the wavelengths ignored by the ISO and ANSI standards. The adoption of a proper UVR definition seems to be critical, considering the fact that most nonglass spectacle lens materials possess high transmittance in the UVA band of wavelengths above 350 nm.…”
Section: Uvr Protection Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…UVR‐mediated mtDNA damage can lead to mitochondrial dysfunction and increased production of ROS in a vicious cycle of increasing damage, leading to a putative increase in photoaging (Figure ) . A study looking at the action spectrum of UVR‐induced mitochondrial damage showed that mtDNA in primary dermal fibroblasts are more vulnerable to damage at UVR wavelengths >320 nm in comparison with nDNA . As mtDNA has limited repair mechanisms, exposure to UVR results in an accumulation of damage, which may accelerate skin ageing.…”
Section: Mitochondria and Photoagingmentioning
confidence: 99%
“…Mitochondrial DNA is particularly vulnerable to damage following exposure to UVR as mitochondria have limited DNA repair mechanisms [8]. A recent study looking at the action spectrum of UVR-induced mitochondrial damage showed that mitochondrial DNA is more vulnerable to damage at UVR wavelengths >320 nm when compared with nuclear DNA [25]. Damage to mitochondrial DNA can lead to mitochondrial dysfunction which may subsequently increase the production of ROS.…”
Section: Sunlightmentioning
confidence: 99%